Nouvelles polarisations politiques en Espagne : l’image de l’adversaire dans les discours de Ciudadanos et Podemos (2014‑2019) - Laure Beltran (Amnis)
From the start of the democratic transition in 1975, Spanish politics, driven by the ghosts of the Civil War, has been characterised by a process of debate and consensus. However, since the 2000’s, this consensual system has been criticised: henceforth, ideological confluence no longer ensured the stability of democracy but instead jeopardizes it. In response to what is considered as an artificial political pluralism, two new political parties emerged in 2016 – Ciudadanos and Podemos. Both are determined to overcome the left-right division which has seemingly lost its identification strength. Therefore, to gain legitimacy they came up with new dichotomisations of the political arena either by claiming to represent « new politics » as opposed to « old politics ». As for Podemos, it adopted a populist strategy standing for the need of an « adversarial » system, thus implementing a fresh antagonism between the people and the elites. This chapter proposes to discuss the discursive strategies employed by the two political groups in order to reorganise the political arena by creating new dichotomies and developing their opponents’ image.